Students' Critical Thinking Skills in Analyzing Literary Works in the Form of Digital Short Stories - R Bahara, Susan; Saiful Latif; Sri Ayu Budi Lestari; Taib Latif; Asmiranda B. Nurhamidin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
One of the skills that 21st-century human resources must have is the capacity for critical thinking. The capacity for critical thinking is the capacity for thoughtful decision-making and problem-solving. This study aims to illustrate how students in the English Language Education Study Program use critical thinking to analyze literary works in the form of digital short tales. The quantitative descriptive approach was employed in this study. 33 students in semester IV were the focus of this study. 6 descriptive questions that were created based on critical thinking skill indicators from Facione (2015) and verified by professionals were used as part of the data collecting approach. The results of the research demonstrated that when examining literary works in the format of digital short tales, self-regulation is a sign of mastery in critical thinking abilities, whereas inference is a sign of difficulty. According to the proportion of students who met the very critical thinking criterion, 21% of students think critically, 27% think less critically, and 43% think very less critically. Of the students, 9% met the very critical thinking criteria. The average score that was earned altogether was 51.1. Consequently, it is evident that the fourth semester English language education study program students' critical thinking abilities fall into the less critical category at Khairun University.